Health consequences of child marriage in high burden countries : a systematic review - Ayuning Aulia; Mieke Savitri (International Journal of Health Science and Technology, 2019)
Child marriage, defined as a formal marriage or informal union before age 18. Worldwide, over 650 million women live today married as children. An estimated 12 million girls under 18 married each year. The purpose of this study is to know health consequences of child marriage. A systematic review by using the search facility database online through PubMed and EBSCO. Journal were screen by using search engine with 5 keywords “child marriage” OR “early marriage” AND “impact” AND “health” then screened based on specific publication from 2013 to 2018, use english, full text, and selecting journals based title and abstract. Found 3822 journals at early stage and at the end 5 articles were included in review. Child marriage significantly increases the likelihood of stillbirth/miscarriage, late child development or stunting, mental health is worse, excessive bleeding, and many women in the ‘thin’/malnutrition category were married before 18 years. There are many health consequences of health marriage. Prevent the occurrence of child marriage, should the child be given education about reproductive health especially, related to the impact of child marriage.